2018
DOI: 10.3389/fimmu.2018.00862
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Phenol-Soluble Modulins α1–α3 Act as Novel Toll-Like Receptor (TLR) 4 Antagonists to Inhibit HMGB1/TLR4/NF-κB Signaling Pathway

Abstract: Phenol-soluble modulins (PSMs) have recently emerged as key virulence determinants, particularly in highly aggressive Staphylococcus aureus isolates. These peptides contribute to the pathogenesis of S. aureus infections, participating in multiple inflammatory responses. Here, we report a new role for S. aureus PSMs in high mobility group box-1 protein (HMGB1) induced inflammation by modulating toll-like receptor (TLR) 4 pathway. Direct ligation of TLR4 with S. aureus PSMα1–α3 and PSMβ1–β2 was identified by sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…Notably, this rearrangement also involved participation of other critical histidine (His431, His555) residues at the TLR4-TLR4* interface [80] unlike the unbound structure (Additional file 8: Figure S5). Overall, these events are congruent with non-canonical TLR4 activation model mediated by microbial peptides, metals and cationic lipid nano-carriers, which are suggested to not confer canonical interaction with other monomers but to induce bond rearrangement among receptor monomers upon interaction [74][75][76][77]. Although the exact mechanism remains to be elucidated, our observations suggest that the vaccine construct may possess a characteristic peptide feature of a non-canonical TLR4 ligand [81,82], which may facilitate TLR4-TLR4* dimerization for downstream activation of immune cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Notably, this rearrangement also involved participation of other critical histidine (His431, His555) residues at the TLR4-TLR4* interface [80] unlike the unbound structure (Additional file 8: Figure S5). Overall, these events are congruent with non-canonical TLR4 activation model mediated by microbial peptides, metals and cationic lipid nano-carriers, which are suggested to not confer canonical interaction with other monomers but to induce bond rearrangement among receptor monomers upon interaction [74][75][76][77]. Although the exact mechanism remains to be elucidated, our observations suggest that the vaccine construct may possess a characteristic peptide feature of a non-canonical TLR4 ligand [81,82], which may facilitate TLR4-TLR4* dimerization for downstream activation of immune cells.…”
Section: Discussionsupporting
confidence: 69%
“…Vaccine-specific, but not parasite protein-specific humoral response was predicted, and this can be used as a biomarker of vaccine efficacy [46,73] without eliciting a parasite-specific B cell response. Moreover, the construct structure showed a good binding affinity in previously reported binding cavity of TLR4 [74][75][76][77].…”
Section: Discussionmentioning
confidence: 70%
“…Vaccine specific, but not parasite protein specific humoral response was predicted, and this can be used as biomarker of vaccine efficacy [38,60] without eliciting parasite specific B-cell response. Moreover, the construct structure showed good binding affinity in previously reported binding cavity of TLR4 [61][62][63][64]. The structural interface between TLR4 and the peptide adjuvant (APPHALS) used here has been extensively studied, in which the position occupied by the adjuvant peptide in the TLR4-MD2 complex has been suggested to be varying depending on its position in vaccine model and canonical activation of receptor was proposed to be mechanized by insertion of peptide adjuvant in MD2 [65].…”
Section: Discussionmentioning
confidence: 88%
“…Inflammation-induced cell damage can Neutrophil-mediated inflammatory response is the main mechanism of liver damage during cholestasis, so the study of specific signaling pathways for concentrated neutrophil aggregation during cholestasis has brought new therapeutic targets for the treatment of cholestatic liver injury. In recent years, studies have found that receptors recognize damage-associated molecular patterns (DAMPs) and thereby activate immune cells, ultimately stimulating a sterile inflammatory response (16).…”
Section: Inflammatory Stress Mediated By the Innate Immune System Durmentioning
confidence: 99%
“…Among the most important PRRs are Toll-like receptors (TLRs), which are a class of transmembrane receptors with a wide distribution. TLR4 is an important PRR that mediates signal transduction (16).…”
Section: Inflammatory Stress Mediated By the Innate Immune System Durmentioning
confidence: 99%